2006
DOI: 10.1080/08958370500434255
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Tobacco Smoke and Coronary Heart Disease Mortality in the United States—A Meta-Analysis and Critique

Abstract: Several major meta-analyses have concluded that exposure to environmental tobacco smoke (ETS) increases the risk of coronary heart disease (CHD) by about 25% among never smokers. However, these reviews have excluded a large portion of the epidemiologic evidence on questionable grounds and have been inconsistent in the selection of the results that are included. We conducted an updated meta-analysis and critique of the evidence on ETS exposure and its relationship to death from CHD among never smokers. Our focu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 32 publications
1
23
0
1
Order By: Relevance
“…Adverse effects of ETS have been reported in epidemiological studies [25,26]. However, I found no air pollution studies that accounted for ETS increments to PM exposures.…”
Section: Indoor Air Pollution Sourcesmentioning
confidence: 93%
“…Adverse effects of ETS have been reported in epidemiological studies [25,26]. However, I found no air pollution studies that accounted for ETS increments to PM exposures.…”
Section: Indoor Air Pollution Sourcesmentioning
confidence: 93%
“…Tobacco industry-funded epidemiological analyses 57,58,73 of large data sets were used to argue against an epidemiological association between SHS and CVD, but these analyses all suffered from exposure misclassification problems that eventually even some in the tobacco industry 71 recognized. More recent industry-funded publications 68,75 report an increased risk of CVD associated with SHS but claim that the magnitude of the risk is far below the generally accepted 30% increase. 7,8 When early tobacco industry-funded work demonstrated that SHS increased atherosclerosis, 39,45,46 the industry criticized the findings for using smoke concentrations larger than that in the real world and withdrew funding.…”
Section: Discussionmentioning
confidence: 99%
“…The authors 75 acknowledged that the non-US studies tended to report higher risks but have 1 sentence stating that inclusion of the non-US studies did not "materially alter" the summary relative risks for the US results, even though their results differed from the risk estimates produced by non-tobaccofunded sources by a factor of 6.…”
Section: Tong and Glantzmentioning
confidence: 99%
See 1 more Smart Citation
“…Die Autoren kommen zu dem Ergebnis: "It seems premature to conclude that environmental tobacco smoke causes death from coronary heart disease and lung cancer" [9]. Fünf Jahre später bekräftigen dieselben Autoren ihre Vorbehalte in einer Metaanalyse etlicher Untersuchungen über das Risiko von Herz-Kreislauf-Erkrankungen [10]. 2009 werden in einem Buch zur Geschichte der Tabakbekämpfung 64 Untersuchungen aufgelistet, von denen 55 keinen statistischen Beleg für angebliche Gefahren des "Passivrauchens" beibringen können [11].…”
Section: Frau Mons Und Frauunclassified